COMPARISON OF DIFFERENT THERMAL AGING PREDICTION MODELS OF CAST AUSTENITIC STAINLESS STEEL - GAO HongBo; YU WeiWei; CHEN MingYa; WU DuAo; CHEN ZhiLin; XUE Fei; ZHEN HongDong; YOU Lei (Jixie qiangdu)
Firstly, the experimental J-R curve and the predicting curves by the three models of 400℃ thermally aged Z3 CN20-09 M pipe and elbow were compared. The results showed that ANL model and H3 T model aren’t suitable for the prediction of low toughness CASS components, however the EDF model is better for low toughness CASS components prediction. All the three models present non-conservative prediction for the early crack propagation, but it doesn’t affect the threshold judgment. According to the comparison between experimental J-R curves and the predicting curves, the ANL model and H3 T model are more suitable for the thermal aging assessment of CASS Z3 CN20-09 M.